Thermoplastic composites prepared from non-woven fibers mat. - Tay , Guan Seng (Universiti Sains Malaysia, 2013)
In this study, non-woven composite was prepared using thermoplastic fiber and two type of lignocellulosic fiber, which is kenaf bast fiber and oil palml empty fruit bunch (EFB). Thermoplastic fiber was mixed with lignocellulosic fiber using carding machine to produce a fiber mat and the fibers in the mat were stitched together by needle punch machine. Then, the fiber mat was hotpressed to produce non-woven composite. The parameters studied in this work were number of needle used in the needle punching process and lignocellulosic fiber loading. Various type of testing were carried out, such as mechanical testing and physical testing. It is found that the mechanical strength of the composite increases as the lignocellulosic fiber was increased, till a threshold value, after which it decreases. This observation is in contrast with previous studies, where the strength of the composites decreased as the lignocellulosic fiber content was increased. The contrast indicates the significance of fiber characteristics as well as fiber arrangements in the matrix towards the mechanical properties of the thermoplastic composites. As for the dimensional stability test, no significant difference is noticed as the number of needle used for needle punching process is increased. However, it can be seen that the water absorption as well as thickness swelling increase with the increase of fiber content.